2015
DOI: 10.1108/sbm-06-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Engaging fans through social media: implications for team identification

Abstract: Purpose – The ubiquity of social media provides sport organizations with opportunities to communicate with fans and as a result, potentially strengthen team identification. The purpose of this paper is to contribute to emerging research on the nature of social media use by sport organizations by examining the platforms adopted over a three-year period by National Basketball Association (NBA) teams and the way in which social media is used to communicate and engage with fans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 42 publications
1
70
0
3
Order By: Relevance
“…Research has mainly explored how social media can be used in the communication efforts of sport organizations and professional athletes (Meng, Stavros, & Westberg, 2015;Wallace et al, 2011;Williams & Downloaded by [94.132.107.225] at 05:48 03 November 2017…”
Section: Social Media Engagement Behaviours: the Cobra Frameworkmentioning
confidence: 99%
“…Research has mainly explored how social media can be used in the communication efforts of sport organizations and professional athletes (Meng, Stavros, & Westberg, 2015;Wallace et al, 2011;Williams & Downloaded by [94.132.107.225] at 05:48 03 November 2017…”
Section: Social Media Engagement Behaviours: the Cobra Frameworkmentioning
confidence: 99%
“…Although academics have claimed there has not been enough research done in this area (O'Shea & Alonso, 2011), there have been a growing number of studies within the field of social media and the influence it has within the sport industry (see Abeza, O'Reilly, Seguin, & Nzindukiyimana, 2015Filo, Lock, & Karg, 2015). While some authors have focused on defining the reasons why individuals (including professional athletes) engage in social media (Hambrick, Simmons, Greenhalgh, & Greenwell, 2010;Mahan, 2011;Meng, Stavros, & Westberg, 2015;Witkemper, Lim, & Waldburger, 2012), others have considered the impact of social media activity on sport brand association and management (Parganas, Anagnostopoulos, & Chadwick, 2017;Wallace, Wilson, & Miloch, 2011), and focused on understanding the different motives for virtual interaction in regards to fans and followers (Gillooly, Anagnostopoulos, & Chadwick, 2017;Jordan, Upright, & Forsythe, 2017;Stavros, Meng, Westberg, & Farrelly, 2014).…”
mentioning
confidence: 99%
“…Athletes have been encouraged to adopt a more active approach in their public presentation via social media (e.g., Lebel & Danylchuk, 2012;Smith & Sanderson, 2015) and to focus their "away from the game" presentation on authenticity (Smith & Sanderson, 2015, p. 355). Sport marketing literature has also revealed that social media is aiding organizations and athletes in increasing fan identification (e.g., Meng, Stavros, & Westberg, 2015;Williams, Chinn, & Suleiman, 2014) and brand awareness (e.g., Na, Kunkel, & Doyle, 2020;Pegoraro, Scott, & Burch, 2017). Social media can create unique and powerful opportunities for high-profile athletes to capitalize on through increased athlete-fan interaction (Pegoraro, 2010) in a cost-effective manner (Filo et al, 2015).…”
Section: Social Media and Sportmentioning
confidence: 99%